World Bank Support to Higher Education in Latvia : Volume 2. Internal Funding and Governance - Arnhold, Nina (World Bank, Washington, DC, 2018)
Focus on Performance - World Bank Support to Higher Education in Latvia. Volume 1: System-Level Funding Since 2013, the World Bank has supported the Latvian government through a succession of advisory work focusing on performance at different levels of the higher education sector. This publication focuses on the development of a performance-based, system-level funding model for the higher education sector in Latvia and consists of three reports: i) Higher Education Financing in Latvia: Analysis of Strengths and Weaknesses; ii) Assessment of Current Funding Model’s “Strategic Fit” with Higher Education Policy Objectives; and iii) Higher Education Financing in Latvia: Final Report. Volume 2: Internal Funding and Governance Since 2013, the World Bank has supported the Latvian government through a succession of advisory work focusing on performance at different levels of the higher education sector. This publication focuses on the analysis of university-internal higher education funding and governance, followed changes at the system-level funding model. It consists of three reports: i) International Trends and Good Practices in Higher Education Internal Funding and Governance; ii) Internal Funding and Governance in Latvian Higher Education Institutions: Status Quo Report; and iii) Internal Funding and Governance in Latvian Higher Education Institutions: Recommendations.. Volume 3: Academic Careers Since 2013, the World Bank has supported the Latvian government through a succession of advisory work focusing on performance at different levels of the higher education sector. This publication focuses on the analysis of the doctorate and human resource policies and on improving academic careers. It consists of three reports: i) Academic Careers: Learning From Good International Practice; ii) Academic Careers In Latvia: Status Quo Report; iii) Academic Careers In Latvia: Recommendations.